Trabectedin and Radiation Therapy for Cardiac Metastasis From Leiomyosarcoma: A Case Report and Review of the Literature - Tortorelli, Ilaria; Navarria, Federico; Maggio, Antonio Di; Banzato, Alberto; Lestuzzi, Chiara; Nicosia, Luca; Chiusole, Benedetta; Galiano, Antonella; Sbaraglia, Marta; Zagonel, Vittorina; Brunello, Antonella (Frontiers in Oncology, 2022)
Leiomyosarcoma (LMS) is one of the most frequent subtypes of soft-tissue sarcomas (STSs). Metastatic spread to the heart in cancer patients carries a poor prognosis, and there is no known effective treatment. Cardiac metastases of STSs are very rare. We here present the case of a 55-year-old patient who underwent surgical resection of a retroperitoneal leiomyosarcoma and then developed widespread metastatic disease, treated with a combination of local treatment and systemic therapy. Three years after surgical resection she presented with a cardiac intraventricular mass, which was treated with radiation therapy, while receiving systemic therapy with trabectedin. Such combination therapy was well-tolerated and effective, allowing a substantial dimensional reduction which is perduring to date, 18 months after diagnosis. Literature available data point at the feasibility and good tolerability of radiation therapy and trabectedin in metastatic sarcoma, yet this is the first report on the effectiveness of the combination for the treatment of cardiac disease. The long survival since metastatic relapse (more than 3 years) is likely the result of integrated systemic and loco-regional treatment, which should be always discussed in the frame of a multiprofessional, multidisciplinary setting.